Antioxidant Effect of Beer Polyphenols and Their Bioavailability in Dental-Derived Stem Cells (D-dSCs) and Human Intestinal Epithelial Lines (Caco-2) Cells - Marina Di Domenico; Antonia Feola; Pasqualina Ambrosio; Federica Pinto; Giovanni Galasso; Armando Zarrelli; Giovanni Di Fabio; Marina Porcelli; Salvatore Scacco; Francesco Inchingolo; Lucio Quagliuolo; Andrea Ballini; et al. (Stem Cells International)
Beer is one of the most consumed alcoholic beverages in the world, rich in chemical compounds of natural origin with high nutritional and biological value. It is made up of water, barley malt, hops, and yeast. The main nutrients are carbohydrates, amino acids, minerals, vitamins, and other compounds such as polyphenols which are responsible for the many health benefits associated with this consumption of drinks. Hops and malt are one of the raw materials for beer and are a source of phenolic compounds. In fact, about 30% of the polyphenols in beer comes from hops and 70%-80% from malt. Natural compounds of foods or plants exert an important antioxidant activity, counteracting the formation of harmful free radicals. In the presence of an intense stressing event, cells activate specific responses to counteract cell death or senescence which is known to act as a key-task in the onset of age-related pathologies and in the loss of tissue homeostasis. Many studies have shown positive effects of natural compounds as beer polyphenols on biological systems. The main aims of our research were to determine the polyphenolic profile of three fractions, coming from stages of beer production, the mashing process (must), the filtration process (prehopping solution), and the boiling process with the addition of hops (posthopping solution), and to evaluate the effects of these fractions on Dental-derived Stem Cells (D-dSCs) and human intestinal epithelial lines (Caco-2 cells). Furthermore, we underline the bioavailability of beer fraction polyphenols by carrying out the in vitro intestinal absorption using the Caco-2 cell model. We found an antioxidant, proliferating, and antisenescent effects of the fractions deriving from the brewing process on D-dSCs and Caco-2 cells. Finally, our results demonstrated that the bioavailability of polyphenols is greater in beer than in the control standards used, supporting the future clinical application of these compounds as potential therapeutic tools in precision and translational medicine.